(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
This research deals with the application of statistical quality control techniques on process control of paracetamol production of Tuyil Pharmaceutical Company with the aim of estimating the control limits and investigate whether the production process is under statistical control. The data used in this research was collected on two measurable quality characteristics of content and weight of paracetamol from 2015-2018. The Mean, Range and EWMA-chart together with process capability analysis were employed for measuring the production process. The result obtained from the analysis on the content of paracetamol, it was observed that for X-bar and R-Chart one point from the observations is out of the control limits while for the EWMA chart all the observations are within control and capable of improving the production process. The analysis also reveals that on the weight of paracetamol, the Mean, Range and EWMA-chart together with process capability analysis are within control and capable of improving the process of production. it was concluded that for the weight of paracetamol is statistically stable and under control while that of the content is partially stable as one point from the observations fall outside the control limits and this could be due to a small shift in the production process which is caused by chance causes of variation such as temperature, room vibration and so on. It is recommended that the company needs to take proper caution so as to improve their production process in order to meet up with consumer’s requirement.